Individualized Interventions: When Teachers Resist - Fasko, Sharla N. (Journal of the American Academy of Special Education Professionals, 2007)
One of the most frustrating situations encountered by special needs professionals is when teachers are unwilling to carry out individualized reinforcement plans for children. Though they are clearly required by law to comply, some individuals still resist our most determined efforts at advocacy. The purpose of this paper is to examine some possible causes of such resistance, and to offer some suggestions for working with these troublesome individuals.